Extraction of the remnant coal pillar in regular and irregular shapes : a case study - Chen, Yong (2020)
With the increasing coal mining rate, many coal mines in China are facing the coal resource exhaustion problem. This paper presents a case study on extracting a coal pillar which was left in a longwall retreat mine, Wangzhuang mine, in China. The left coal pillars usually have boundaries of regular and irregular shapes, which result in complex stress distributions within the coal pillar. It is of great importance to study the stress distributions and to determine the roadway layout prior to extracting the left coal pillar. This study numerically analyzes the stress distributions in the left coal pillar, based on which the roadway layout and support techniques are proposed. The roadway stability were well maintained throughout the mining process and the mining safety and productivity were ensured. The left coal pillar in Wangzhuang mine was successfully extracted. This case study would be helpful for extracting the left coal pillar in the longwall retreat mines.